Race mixture in nineteenth-century U.S. and Spanish American fictions : gender, culture, and nation building - Rosenthal, Debra J., 1964- (University of North Carolina Press, 2004)
Race mixture has played a formative role in the history of the Americas, from the western expansion of the United States to the political consolidation ofLatin America. This text examines 19th-century authors in the United States and Spanish America who struggled to give voice to contemporary dilemmas about interracial sexual and cultural mixing.
Keywords: Nervo, Amado; Lateinamerika; Universidad Sergio Arboleda; American fiction -- 19th century -- History and criticism.; Miscegenation (Racist theory) in literature.; Spanish American fiction -- 19th century -- History and criticism.; Comparative literature -- American and Spanish American.; Comparative literature -- Spanish American and American.; Multiracial people in literature.; Race relations in literature.; Slavery in literature.; Racism in literature.; Race in literature.; Roman américain -- 19e siècle -- Histoire et critique.; Métissage dans la littérature.; Roman hispano-américain -- 19e siècle -- Histoire et critique.; Littérature comparée -- Américaine et hispano-américaine.; Littérature comparée -- Hispano-américaine et américaine.; Métis dans la littérature [Annulée]; Relations raciales dans la littérature.; Esclavage dans la littérature.; Racisme dans la littérature.; Race dans la littérature.; LITERARY CRITICISM -- American -- General.; American fiction; Miscegenation (Racist theory) in literature; Race in literature; Race relations in literature; Multiracial people in literature; Racism in literature; Slavery in literature; Spanish American fiction; Rassenvermenging.; Letterkunde.; Spaans.; Amerikaans.; Amerika; Miscegenation in literature.; Racially mixed people in literature.; 1800-1899; Criticism, interpretation, etc.